Teacher Teams in Compulsory Secondary Education: Possibilities and Uncertainties - González González, Mª Teresa (Education Policy Analysis Archives, 2007)
This paper is about the constitution of teacher teams in the Educación Secundaria, something proposed in the Ley Orgánica de Educación (LOE, 2006). First, a discussion of the disadvantages of organizing high schools by academic departments is presented, namely, the tendency of teachers to communicate mainly with those colleagues working in the same curricular area, the difficulties involved in the development of curricular projects that translate into globally coherent school experiences meaningful and relevant for the students, and the repercussions of such structures on the caring and support for students. Against this background, it is suggested that one of the alternatives to counteract the effects of departmentalization entails the creation of teacher teams. The new possibilities of coordination offered by teams are then commented, as they are seen as appropriate instruments to articulate the work and reflection of their members on cross curricular issues. Finally, some uncertainties and complexities of this new structure are discussed, namely, the possibility of it being applied only at a formal level, the difficulties involved in the coexistence of teams and departments, or the risk of overlooking the ”instituto” as a globally oriented educational institution.